2023
DOI: 10.3390/f14050868
|View full text |Cite
|
Sign up to set email alerts
|

Forest Gaps Slow the Humification Process of Fir (Abies faxoniana Rehder & E.H.Wilson) Twig Litter during Eight Years of Decomposition in an Alpine Forest

Abstract: Litter humification plays a crucial role in organic matter formation and soil carbon sequestration in forest ecosystems. However, how forest gap formation and gap size variation affect the litter humification process remains poorly understood. An eight-year in situ decomposition experiment was conducted to evaluate humus accumulation (humic substances, humic and fulvic acid), humification degrees, humification ratios and optical properties (ΔlogK, E4/E6 and A600/C) of Minjiang fir (Abies faxoniana Rehder &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 82 publications
1
2
0
Order By: Relevance
“…However, the magnitude of N release was greater in the forest gap than that in the understorey, suggesting that canopy structure may modulate the effect of solar radiation on N dynamics during litter decomposition. Similar results have been detected in various litter types, such as leaves, twigs, and logs (Wang et al 2023(Wang et al , 2022bWu et al 2023).…”
Section: Pre-exposure To Autumn Solar Radiation Has a Positive Legacy...supporting
confidence: 85%
See 1 more Smart Citation
“…However, the magnitude of N release was greater in the forest gap than that in the understorey, suggesting that canopy structure may modulate the effect of solar radiation on N dynamics during litter decomposition. Similar results have been detected in various litter types, such as leaves, twigs, and logs (Wang et al 2023(Wang et al , 2022bWu et al 2023).…”
Section: Pre-exposure To Autumn Solar Radiation Has a Positive Legacy...supporting
confidence: 85%
“…The reduction in forest canopy closure is the dominant form of disturbance due to changes in land-use (e.g., deforestation and clear felling). Together with climatic drivers, the increase in sunlight exposure gaps facilitates the litter decomposition of leaves, twigs, and logs (Chen et al 2023;Wang et al 2022b), and slows litter humification process (Wu et al 2023), enhancing ecosystem C release. Our recent study has found that exposure to the full-spectrum when a forest gap opens can greatly increase litter decomposion rate by almost 120% across a wide range of species (Wang et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Carex myosuroides Vill. and a variety of grass vegetation mostly grow in the dark felty soil, and it is an important area for livestock products [30]. The vegetation in the alpine meadows is mainly Kobresia humilis and Carex alatauensis S. R. Zhang, and the accompanying species include Carex tristachya Thunb.…”
Section: Study Areasmentioning
confidence: 99%